2003
DOI: 10.1345/aph.1c365
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Inappropriate Medication Use in Community Residential Care Facilities

Abstract: Potentially inappropriate medication use is common among residents in CRC facilities. A comprehensive periodic review may be beneficial for reducing potentially inappropriate use, especially for patients taking multiple drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 23 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…34 Three of the nine studies 20,25,27,2934 investigating race found racial determinants of PIM use, but the directions differed by the studied population. 25,31,33 Marital status, 26,33 poverty, 26 education, 26,30,31,34 and length of stay 26,28,33 were not significant determinants of PIM use.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…34 Three of the nine studies 20,25,27,2934 investigating race found racial determinants of PIM use, but the directions differed by the studied population. 25,31,33 Marital status, 26,33 poverty, 26 education, 26,30,31,34 and length of stay 26,28,33 were not significant determinants of PIM use.…”
Section: Resultsmentioning
confidence: 91%
“…20,2426,30,3234 Less impairment in activities of daily living was associated with PIM use in three. 25,26,32 Among residents with severe dementia, severe medical illness as indicated by hospitalization in the last 90 days or a recent physician visit were associated with more PIM use.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The use of residential care in this population, and errors involving psychotropics in residential care facilities are both common (Sloane et al, 2002;Gray et al, 2003Gray et al, , 2006. A cohort study of adverse drug events (an injury from either an error in prescribing/ physician ordering, dispensing, administration or monitoring, or an adverse drug reaction not associated with an error) in 1,247 long-term care residents (mean age 86 years) found that of all medication classes, anti-psychotics were associated with the greatest risk of an error (adjusted OR 3.4; 95% CI: 2.0 to 5.0; Gurwitz et al, 2005).…”
Section: Potential Risk Factorsmentioning
confidence: 99%
“…Inappropriate or suboptimal drug prescribing has been documented in older adults who are indigent, homeless, community dwellers, nursing home residents, assisted-living residents, and inpatients. 133,[177][178][179][180][181][182][183][184] Pharmacist impact on inappropriate or suboptimal prescribing and ADRs has been examined either as economic savings or changes in health care outcomes. However, more research is needed to document the impact of a pharmacist on eliminating drugrelated problems and the development of new types of pharmacy services.…”
Section: Research Gaps and Opportunities For Pharmacy And Older Adultsmentioning
confidence: 99%